Creating Ethical and Eco-friendly Communities in Amitav Ghosh’s The Glass Palace - Vincent, Suhasini (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
In this paper, we shall see the materialistic intent behind the British invasion of Burma and their lucrative teak trade. We shall explore how Amitav Ghosh presents the problems of conserving biodiversity, distrusts materialistic forces that crush indigenous dissent, and takes part in the new emerging paradigm of making a Material Turn. He thus considers possible ways of analysing language and reality, human and non-human life, mind and matter, without falling into dichotomous patterns of thinking. Ghosh has often probed into the reasons for the postcolonial writer's imaginative failure in the face of ecological devastation. He examines the inability of the present generation to speak of the loss of the habitat and posits that this indifference is reflected in the postcolonial literature of our time, in the recording of colonial history, and the political ambiance of our day. Ghosh posits that writers need to find new modes of thinking, create imaginative forms of fiction where ethical, and inspire the existence of ethical, eco-friendly communities.